PERILAKU PRODUSEN DALAM ETIKA BISNIS ISLAM (SUATU UPAYA PERLINDUNGAN KONSUMEN) - Ermawati Usman (State Institute of Islamic Studies (IAIN) Palu, 2007)
A component to the utility of resources in the field of economy is producen. Through a business-oriented produsen for the benefit of both wordly life and hereafter life, a utility of resources for the whole mankind will be esatbelished. In this respect, resources created by the Almighty God always has a utility for mankind and their surroundings. It is here that as a way of life, Islam possesses a complete and firm rule for all fields of life including economy. Therefore, as a producen, mankind must meet ethichal standard as stipulated in the Islamic business ethics Kata Kunci: Produsen, produksi, etika bisnis Islam, konsumen